Implementasi Kurikulum Adaptif untuk Anak Berkebutuhan Khusus: Sebuah Tinjuan Literatur - Fajar Sidik; Rofi'i, Agus; Diana, Diana (Jurnal Ilmiah Edukatif, 2025)
An adaptive curriculum allows for learning that is more responsive to the individual needs of students, who differ in terms of learning pace, interests, and learning styles. With a flexible curriculum, teachers can adapt materials and teaching methods to accommodate these differences, creating a more inclusive and effective learning environment. This study aims to examine the implementation of an adaptive curriculum for children with special needs through a comprehensive literature review. The results of the review show that an adaptive curriculum can significantly improve the engagement and academic success of children with special needs by providing a personalised approach based on the strengths, weaknesses, interests, and individual needs of each student. Effective implementation requires the role of trained teachers, technological support, active parental participation, and synergy between school, home, and community. In addition, supportive government policies, including clear regulations and adequate budget provision, are crucial to the successful implementation of this curriculum. Overall, this literature review confirms the great potential of the adaptive curriculum in improving the quality of education for children with special needs, noting the importance of continuous multi-dimensional support.